The Macedonian Dispute in the Activity of the Metropolitan of Thessalonica Anthimos - Dragouni, Olimpia (Poznańskie Studia Slawistyczne, 2016)
The article focuses on a context rarely exposed yet significant for the analysis how the Macedonian Dispute is perceived by the Greek public opinion. The aim of the text is to show the position of the representatives of the Orthodox Church of Greece with a special attention dedicated to the Metropolitan of Thessalonica Anthimos. The extensive quotations from different statements by the Holy Synod of the Greek Orthodox Church and the Metropolitan of Thessalonica (sermons, interviews, publications) are interpreted. The idea is to help the reader with no or a weak command of Greek language to show the background, shape and key concepts of Greek criticism regarding Macedonian issue. Moreover, the aim is to show the influence of sacral and secular sphere over the politics.